2005
DOI: 10.1111/j.1467-8535.2005.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance in e‐learning: online participation and student grades

Abstract: The beneficial effects of learners interacting in online programmes have been widely reported. Indeed, online discussion is argued to promote studentcentred learning. It is therefore reasonable to suggest that the benefits of online discussion should translate into improved student performance. The current study examined the frequency of online interaction of 122 undergraduates and compared this with their grades at the end of the year. The findings revealed that greater online interaction did not lead to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
240
3
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(306 citation statements)
references
References 7 publications
(8 reference statements)
28
240
3
8
Order By: Relevance
“…The Electronic Journal of Information Systems in Developing Countries www.ejisdc.org activities was significantly associated with their grades in a study conducted at University of Glamorgan, UK with 122 students (Davies & Graff, 2005). Similar findings were obtained in studies conducted in various institutions (e.g.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…The Electronic Journal of Information Systems in Developing Countries www.ejisdc.org activities was significantly associated with their grades in a study conducted at University of Glamorgan, UK with 122 students (Davies & Graff, 2005). Similar findings were obtained in studies conducted in various institutions (e.g.…”
supporting
confidence: 73%
“…Calculating the total amount of time spent between login and logout (Davies & Graff, 2005;Mödritscher et al, 2013;Yu & Jo, 2014) 3.…”
Section: Time Spent In the Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies observed that more peer interactions generate higher academic performance [37,38]. On the contrary, another study concluded that students with higher grades tend to read less of the forum content than those with lower grades [35].…”
Section: Individualistic Vs Connectivist Moocsmentioning
confidence: 99%
“…• Davies and Graff [5] indicate that the number of times a student logs into the system (Blackboard) can be used as an effective indicator to quantify the student's engagement.…”
Section: Introductionmentioning
confidence: 99%